Flower beverages of native medicinal plants from Argentina (Acacia caven, Geoffroea decorticans and Larrea divaricata) as antioxidant and anti-inflammatory. (5th December 2021) - Isla, María Inés; Ezquer, María Elisa; Leal, Mariana; Moreno, María Alejandra; Zampini, Iris Catiana
Abstract: Ethnopharmacological relevance: Herbal beverages have been used as a natural part of the medicinal and food culture in northwestern Argentina. The flower beverages (infusion or decoction) of Acacia caven, Geoffroea decorticans and Larrea divaricata, three native species from arid and semiarid regions of Argentina are widely used as anti-inflammatory and anti-rheumatic by several local communities. Aim of the study: The aim of this study was to analyze the phytochemical composition of some Argentine flower beverage and to validate its traditional use as an antioxidant and anti-inflammatory agent. Materials and methods: Phenolic profiles from all flower infusions and decoctions were analyzed by both spectrophotometric analysis and HPLC-DAD. ABTS + ; the scavenging activity of both hydrogen peroxide and hydroxyl radical was determined and finally, their ability to inhibit pro-inflammatory enzymes, such as xanthine oxidase (XOD), and lipoxygenase (LOX) was also assessed. Results: The flower beverages of all assayed species showed a high level of phenolic compounds with similar chromatographic patterns in both infusions and decoctions of each plant species, the major components of which have been identified. The flower beverages, especially G. decorticans infusion and decoctions, displayed an important antioxidant activity (SC50 values between 18.14 and 47 μg/mL) through different mechanisms; all of them were able to inhibit the XOD enzyme activity and, consequently, the formation of uric acid and reactive oxygen species, the primary cause of arthritis-related diseases. The most active beverages as XOD inhibitor were G. decorticans flower infusion and decoctions (IC50 values of 20 and 35 μg/mL, respectively). Pro-inflammatory enzymes, such as LOX, were also inhibited by infusions and decoctions of G. decorticans, L. cuneifolia and A caven flowers, lessening inflammation mediators in all beverages. Conclusions: The present work validates the traditional medicinal use of flower beverages from Argentina as an anti-rheumatic and anti-inflammatory agent as it has been used for hundreds of years in several pathologies associated with oxidative stress. Graphical abstract: Image 1